Clinical Reasoning Assessment in Portuguese Medical Schools - Ruas, Pedro; Nunes, Célia; Neto, Isabel (Spanish Journal of Medical Education, 2025)
Introduction: Clinical reasoning is essential for medical practice. Assessing this competency in undergraduate education plays a vital role in preventing medical error; hence, it should be conducted with basis on the best international practices. However, knowledge regarding the assessment of clinical reasoning in Portuguese medical schools is currently limited. This study aims to deepen the current understanding of clinical reasoning assessment in Portugal by analyzing the prevalence of various common assessment methods and identifying their main associated barriers. Materials and Methods: A survey was administered between May to July 2023 to all faculty members responsible for curricular units in the senior years of the Medical Integrated Master's degree in Portugal. The SPSS® software, version 28.0 for Microsoft Windows®, was used. Data was predominantly analyzed through descriptive statistics. Results: 75 responses were collected from 8 medical schools in Portugal, representing roughly half of the target population. The majority of faculty members have over 30 years of experience in assessment. Multiple-choice questions is the most used method of assessment. Methods applied in simulated and clinical environments, particularly the direct observation, were perceived to be in considerable deficit in the curricula. The main identified barriers include lack of faculty time and human resources. Conclusions: There is a need for an increased implementation of methods in simulated and clinical environments, allowing for a more comprehensive assessment of clinical reasoning. In order to achieve this, more investment in human resources is pivotal, namely by increasing faculty recruitment and promoting more training courses on clinical reasoning assessment.